PENGARUH LATIHAN ALTERNATE LEG BOX BOUNDS TERHADAP EXPLOSIVE POWER OTOT TUNGKAI PADA TIM BULOG VOLI BALL CLUB JUNIOR PEKANBARU - Azman Azman; Ramadi Ramadi; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract. The research has been done to find out whether there is any influence towards Alternate Leg Box Bounds exercise to Explosive Power Of Muscle Limbs Of Bulog Valleyball Club Junior Pekanbaru, until it is done the smash jumping and blocker to get the best jumping. The type of the research is experiment, the population is Bulog Volley Ball player at Volley ball club junior pekanbaru. The data of this research is the whole population consists of 12 people. The instrument used in this research was Vertical Power Jump Test, which has purpose to measure the strengthen of muscle limbs. After that, the data processes using statistic. To test the normality with lilifors test in the fase of significant 0,05α. The hypothesis proposed was there any influence Alternate Leg Box Bounds towards power muscle limbs explosive. Based on the anaylisis of t tes resulting 5,51 and Ttab1,796. It means thatTcount >Ttab. Based on the statistic data analysis, the data was normal. Therefore, there was influence Alternate Leg Box Boundstowards muscle limbs power explosive in Volleyball Bulog Team Volleyball Junior Club Pekanbaru.Keywords : Leg Box Bounds, Explosive Power of Muscle Limbs